2002
DOI: 10.1046/j.1365-2621.2003.00665.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of phenolic extracts obtained from the olive plant (cvs. Picual and Kronakii), on the stability of sunflower oil

Abstract: Summary The phenolic compounds of olive cultivars (Picual and Kronakii) were extracted. The total phenolic content of the extracts was estimated and their ability to reduce the oxidation of sunflower oil was tested at 100 °C by using a Rancimat®. The fruits, leaves and pomaces were extracted separately with ethanol. Portions of the fruits were crushed to produce an oil/aqueous mixture, which was separated and the two fractions further processed. The oil fraction was extracted with 60% aqueous methanol and was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
59
0
6

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(73 citation statements)
references
References 21 publications
(24 reference statements)
6
59
0
6
Order By: Relevance
“…Phenolic compounds widely distributed in the natural plant tissues include flavonoids, tannins, hydroxycinnamate esters, and lignins (Rice-Evans et al, 1997). Furthermore, interest in employing antioxidants from natural sources to increase the shelf life of foods is considerably enhanced by consumer preference for natural ingredients and concerns about the toxic effects of synthetic antioxidants (De Lenardis & Macciala, 2003;Farag, 2003;Schwarz, 2001;Tang, 2001). The Hypericum family seems to be a rich source of plant species containing large amounts of phenolic acids, so it is considered to be a promising source of natural antioxidants (Conforti et al, 2002;Silva, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Phenolic compounds widely distributed in the natural plant tissues include flavonoids, tannins, hydroxycinnamate esters, and lignins (Rice-Evans et al, 1997). Furthermore, interest in employing antioxidants from natural sources to increase the shelf life of foods is considerably enhanced by consumer preference for natural ingredients and concerns about the toxic effects of synthetic antioxidants (De Lenardis & Macciala, 2003;Farag, 2003;Schwarz, 2001;Tang, 2001). The Hypericum family seems to be a rich source of plant species containing large amounts of phenolic acids, so it is considered to be a promising source of natural antioxidants (Conforti et al, 2002;Silva, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…It was found that enrichment with olive leaf extracts is sufficient to fortify refined oil to a similar stability as a virgin olive oil (Paiva-Martins et al, 2007). Likewise, it was reported that phenolic extracts obtained from the olive plant (fruit, leaves and pomace) showed remarkable antioxidant activity in retarding sunflower oil oxidative rancidity (Farag et al, 2003). Therefore, olive leaves can be considered a cheap raw material and a safe and natural potential of antioxidants.…”
Section: Dpph Assaymentioning
confidence: 99%
“…Further, olive leaves are considered as a cheap raw material which can be a source of high-added value products (Briante et al, 2002). Indeed, recent research has demonstrated that olive leaves are a good source of phenolic compounds, such as secoiridoids and flavonoids which have strong protective effects against oil oxidation (Farag et al, 2003;PaivaMartins et al, 2007) and a positive impact on human health (Japon-Lujan and Luque de Castro, 2006;Altiok et al, 2008). Several reports have shown that the olive leaf has the capacity to lower blood pressure (Khayyal et al, 2002) and increase blood flow in the coronary arteries (Zarzuelo 1991).…”
Section: Introductionmentioning
confidence: 99%